WE4.6 Postoperative muscle atrophy: an overlooked cause of morbidity. (9th August 2022) - Hardy, Edward; Hatt, Jacob; Doleman, Brett; Phillips, Beth; Lund, Jon
Abstract: Aims: A significant proportion of patients never fully recover baseline activity levels following major abdominal surgery. Postoperative muscle atrophy may be a major contributing factor to this, but is often overlooked. This study aimed to quantify the degree of muscle loss in patients undergoing routine recovery following major abdominal surgery and in patients admitted to critical care. Methods: Fifteen patients undergoing major open colorectal resection were recruited. Cross surface area (CSA) and muscle thickness (MT) of a quadriceps muscle, Vastus Lateralis (VL) were measured pre-operatively and on post-operative day (POD) 5 using ultrasound. Knee extension strength was also measured pre-operatively and on POD5 using a handheld dynamometer. A systematic literature review was performed to identify studies reporting muscle loss in patients admitted to an intensive treatment unit (ITU), with pooled means of changes in quadriceps muscle CSA calculated. Results: By POD 5 VL CSA had decreased by 9.16% (± 2.0), and MT had decreased by 8.14% (± 5.93). Associated with this, knee extensor strength decreased by 19.69% (± 12.91). Systematic review identified 4 studies reporting muscle loss in ITU patients, including a total of 126 patients. Pooled mean of quadriceps CSA in patient admitted to ITU decreased by 13.9% (-12.5% -20.75%) by POD7. Conclusions: Major abdominal surgery is associated with a significant loss of muscle mass and function. Losses are larger in patients requiring ITU admission. This may have a significant impact on patients' full recovery to baseline function and further work is required to investigate this.